Hide information usings cryptography based on android platform / Ahmad Farhan Ahmad Husni - Ahmad Husni, Ahmad Farhan (2013)
The high technology of hand phones today makes people prefer to use their mobile phone than computer to passes their sensitive information through internet. Without they realize, these technology can bring their confidential or private information being attack from unauthorized party and lead to information leakage. These unauthorized party that mention here is Man in The Middle Attack (MiTM). Man in The Middle Attack (MiTM) can manipulate and give false information to the sender. This problem can cause a big impact to the businessman when they do trading transaction. To solve the problem, a steganography tool is developed to help to hide the secret message before being sent through the internet. This project focuses on steganography and cryptography. This application uses two levels of securities that make the information more secure and bring difficult to unauthorized party get the information. The cryptography will use the DES algorithm to hide the message before hiding the information into an image by using steganography. DES algorithm uses public-key system means the algorithm for encrypting and decrypting a message is public know. This application will run on the android platform. This project aims to successfully encrypt and decrypt the message to protect the message from unauthorized person.